Penerapan Intervensi Edukasi Pendidikan terhadap Fatigue pada Pasien Hemodialisis (Journal of Telenursing (JOTING), 2023)
This research aims to implement education on fatigue in hemodialysis patients. The method used was a Randomized Controlled Trial with a quasi-experimental research design. The results showed a significant difference in the average total Fatigue score in the experimental and control groups after participating in the program (P < 0.001). There were also statistically significant differences between age, gender, disease duration, dialysis frequency, and Fatigue level (p